Kajian Strategis Pemekaran Kecamatan di Daerah Perbatasan (Studi Pemekaran Kecamatan Sugie Besar Kabupaten Karimun Provinsi Kepulauan Riau) - Oksep Adhayanto; Handrisal Handrisal; Irman Irman (Jurnal Selat, 2016)
Law Number 23 Year 2014 About the local government, said that the Regional (district / city) can form the districts in order to improve the coordination of governance, public services, and the empowerment of village communities / villages. Karimun Regency is one of regencies in Riau Islands Province, which borders directly with Singapore. The geographical position of Karimun regency consists of several islands large and small impede access to public services. Therefore, expansion of the existing sub-district is one alternative solution in order to improve the welfare of society. The purpose of this research is to study the prospective analysis of the division of the sub-district of the District Parent Sugie Moro based on Government Regulation No. 19 Year 2008 on the District. The design study is descriptive analysis with qualitative and quantitative approach, where data in the form of empirical reality analyzed qualitatively by describing and considering the provisions of the normative, theoretical judgment or views of experts and key informants related to expansion efforts districts. The results of this study are candidates for the District Sugie Besar only meet one of three requirements formation of districts, namely the requirements of the technical requirements. As for the physical requirements of the administrative and territorial unfulfilled. Candidates for the technical requirements of the District of Sugie Besar Acquire Score 368 which is in the category and Recommended Able to be formed into new districts. While the District Parent Moro after bloomed (formed District of Sugie Besar) they meet one of three requirements of establishing districts as set out in Regulation No. 19 Year 2008 on the District, namely the requirement of technical requirements, while for the administrative and physical cantonal requirements are not met. For the technical requirements, the District Parent Moro obtain a score of 391 in the category Ability and Recommended. The conclusion from this study is that although only meet one of three requirements formation of districts, the Government of Karimun Regency will still be able to carry out the formation of the District Candidate Sugie Besar. It is possible as a rule, that the district / city government can be formed districts in the region that includes one or more islands, which requirements are exempt from the administrative requirements, terms of physical territoriality, and technical requirements as those mentioned with consideration to the effectiveness and efficiency of service delivery and community empowerment village on the remote islands and / or outer. Keywords : Expansion , Expansion Districts, Border Region , the Sugie Besar